Ethanolic Extracts of Cupressaceae Species Conifers Provide Rapid Protection against Barium Chloride-Induced Cardiac Arrhythmia - Meng-Ting Zeng; Li-Yue Huang; Xiao-Hui Zheng; Yan-Qi Fu; Ching-Feng Weng (MDPI AG, 2024)
Sudden cardiac death (SCD) is responsible for a high percentage of cardiovascular fatalities, with ventricular arrhythmias being the most common cause. Despite numerous clinically available antiarrhythmic drugs (AADs), AADs retain some undesirable arrhythmic effects, and their inappropriate use can lead to severe adverse reactions. The exploration of new therapeutic options against arrhythmias with fewer unreceptive effects is of utmost importance. The ethanolic extracts of seven Cupressaceae species, namely, Chamaecyparis obtusa, Juniperus chinensis (L.) Ant., Sabina chinensis (L.) Ant. cv. Kaizuca, Platycladus orientalis (L.) Franco, Juniperus sabina L., Fokienia hodginsii, and Juniperus chinensis 'Pyramidalis' were investigated for their pharmacological effects on barium chloride (BaCl2)-induced arrhythmia using normal II lead electrocardiogram (ECG) measurements in a mouse model. According to the ECG profiles, pretreatment with C. obtusa, P. orientalis, and J. sabina extracts provoked dose-dependent protection against BaCl2-induced arrhythmia, while pretreatment with the other four species and amiodarone did not exert cardioprotective effects. The treatment effects were confirmed using a rat model. The therapeutic effects of C. obtusa, P. orientalis, and J. sabina extracts on the M2 and M3 receptors but not the M1 receptor were mediated by the inhibition of the M2 receptor blocker (methoctramine tetrahydrochloride), M3 antagonist (4-DAMP), or M1 receptor blocker (pirenzepine dihydrochloride). This first-line evidence illustrates that certain Cupressaceae species possess active antiarrhythmic components. The first line of key findings revealed that active components of certain Cupressaceae species have cardioprotective effects, suggesting that these innovative phytochemicals have promising potential for preventing the occurrence of cardiac arrhythmia and reducing sudden cardiac death.